Extended-spectrum β-lactamase Enterobacteriaceae from patients in Jeddah, Saudi Arabia: Antibiotic susceptibility and molecular approaches - Alshehri, Wafa A.; Moussa, Tarek A. A. (Journal of Contemporary Medical Sciences, 2021)
Objectives: This study aimed to determine the Enterobacteriaceae strains among patients who suffering diarrhea, phenotypic and genotypic characterization of ESBL-producing isolates in Jeddah, Saudi Arabia. Methods: Stool samples were collected and cultured to determine the different Enterobacteriaceae strains, PCR was done for the isolates to detect the different ESBLs genes and antibiotic susceptibility against different antibiotics was done. Results: The total number of patients in this study was 200 (114 males [57%] and 86 females [43%]). The patients were categorized to teenagers (21, 10.5%), adults (92, 46%), middle age (25, 12.5%) and elderlies (25, 12.5%) according to age. Five Enterobacteriaceae strains was found: Enterobacter cloaca (7, 3.5%), Escherichia coli (111, 55.5%), Klebsiella pneumoniae (75, 37.5%), Proteus mirabilis (6, 3.0%) and Pseudomonas aeruginosa (1.0, 0.5%). P. aeruginosa was absent in all female patients under investigation. The response of the isolated (E. coli, K. pneumoniae and E. cloaca) strains to ampicillin, cefotaxime, cefotaxime-clavulanate, ceftriaxone, cephalothin and chloramphenicol, ciprofloxacin, nalidixic acid, streptomycin, tetracycline and trimethoprim-sulphamethoxazole was highly resistant, while the response was highly susceptible to ampicillin sulbactam, ceftazidime, ceftazidime-clavulanate, and imipenem. The most frequent gene was blaCTX-M (195) followed by blaTEM (149), blaSHV (73) and blaOXA (3), while the highest pair of genes in the same organism was blaTEM+blaCTX-M (134) followed by blaSHV+blaCTX-M (64), blaSHV+blaTEM (52) and the least pairs were blaTEM+blaOXA (3) and blaCTX-M+blaOXA (2). blaSHV+blaCTX-M+blaTEM was found in 44 organisms and blaCTX-M+blaTEM+blaOXA in two organisms only. The blaSHV+blaOXA, blaSHV+blaCTX-M+blaOXA, blaSHV+blaTEM+blaOXA and blaCTX-M+blaTEM+blaOXA+blaSHV were not present in any organism under investigation. Conclusion: In teenager group, there were no organism contain blaOXA gene, while blaOXA present in E. cloaca and P. mirabilis only. blaSHV gene was absent in E. coli but present in E. cloaca and K. pneumoniae. The most susceptible group to infection with Enterobacteriaceae was adults' group, while teenage was more resist to infection.